Os portos marítimos na mundialização do capital - Galvão, Cassia Bömer (2009)
The aim of this study is to analyze the changes in the maritime ports sector considering the recent economic liberalization with consequent substantial growth in the international trade and therefore increasing demand for sea transport of goods. This situation leads to a reflection about its determinant factors and consequences as it is evident that the growth in the international trade not followed by growth in the global production has caused several changes in the transport infra-structure, especially in the port sector. This process was particularly accelerated during the 1990 s, but the changes in the transport have started already in the 1980 s with the general usage of the containers. In this context, the role of maritime ports become more important, as they are the preferential mode used for the international trade transactions. The ports, therefore reveal to be (among other factors) key element for the competitiveness of international prices. Thus, as all these chances are not caused by an abstract or independent modernization wave, but they belong to a major context of new economic scenario (the globalization); it is relevant to know the details of this new port infrastructure. In the case of Brazilian ports there are two issues in focus: first the changes promoted by the Modernization Law (1993), considered to be the main legal document in the new port management and format in Brazil; and second the perspectives for the port sector in the future, considering the new investment proposition in the PNLT (National Plan for Logistics and Transport). The results of this study show that the ports have an essential role in the new logistics concept, which was developed to attend the need of new lean production. This means that the port reforms, made during the 1990 s, present a deep relation with dislocation phenomenon and globalization of capital